Economic and demographic factors affecting the economic participation of rural women in the provinces of Iran with emphasis on the age- participation curve - ZahraMila Elmi; mahsa khanekeshi (فصلنامه زن و جامعه, 2023)
we study the effects of socio-economic and demographic factors on women's economic participation in rural areas of Iran's provinces with emphasis of age-participation curve. Therefore, this study was performed by using the results of the rural households’ income and expenditure survey -has been taken in 2016- in the framework of Pseudo-Panel Data. We used the logit model and the maximum likelihood method to study the rural women's participation, with 28,265 observations. Results show the inverted U-shaped relationship between age and the probability of female participation; In other words, young women are more likely to participate in labor markets more than the other groups. Divorced and single woman has more likely to participate in comparison with who was being married. Therefore, with increasing the divorce rate and singleness in Iran, economic policymakers must provide appropriate solutions for this challenge in the coming years. We found that women studying and the presence of an infant under the age of 6 in the household has a negative effect on the possibility of women's participation in the labor market. The female education has positive effect on their participation rate. In the overlook, considering the demographic mirror and due to the frequency of the women population in the age group of 25 to 35 years, and more willingness of women in the age 35 to 44 years to participate in the labor market, and education of a significant portion of the rural women, the increase of rural female participation is expected in the years ahead.